2003
DOI: 10.1099/mic.0.25936-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the nos genes for nitrous oxide reductase in Pseudomonas aeruginosa

Abstract: The genes for nitrous oxide (N 2 O) reduction, nosRZDFYL, are clustered on the chromosome of Pseudomonas aeruginosa. Promoter assays using transcriptional fusions to lacZ revealed that the structural gene for nitrous oxide reductase, nosZ, is transcribed with the upstream nosR gene. The nosR gene product is not required for the activity of the nosR promoter. A sequence similar to the consensus FNR-binding motif was found 41?5 bp upstream from the major transcriptional start point of nosR. Mutation of the motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 45 publications
(36 reference statements)
7
105
0
Order By: Relevance
“…Previous studies, carried out in P. aeruginosa PAO1 with the nirS, the norC and the nosZ promoters fused to the lacZ reporter gene, showed that the DNR transcription factor responds in vivo to N-oxides (Arai et al, 1999(Arai et al, , 2003. A similar response to NO in vivo has been reported for the DNR homologue NNR in Paracoccus denitrificans (Van Spanning et al, 1999) and, for the same regulator, also in E. coli using the FNR-dependent E. coli melR promoter (Hutchings et al, 2000).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies, carried out in P. aeruginosa PAO1 with the nirS, the norC and the nosZ promoters fused to the lacZ reporter gene, showed that the DNR transcription factor responds in vivo to N-oxides (Arai et al, 1999(Arai et al, , 2003. A similar response to NO in vivo has been reported for the DNR homologue NNR in Paracoccus denitrificans (Van Spanning et al, 1999) and, for the same regulator, also in E. coli using the FNR-dependent E. coli melR promoter (Hutchings et al, 2000).…”
Section: Introductionsupporting
confidence: 58%
“…In P. aeruginosa the denitrification pathway is regulated by redox signalling, through a cascade of transcription factors; in particular, the global oxygen-sensing regulator ANR (anaerobic regulation of arginine deaminase and nitrate reduction) (Galimand et al, 1991), a homologue of the Escherichia coli oxygen sensor FNR protein, activates, under anaerobic conditions, the gene coding for the transcription factor DNR (dissimilatory nitrate respiration regulator), which, in the presence of N-oxides, promotes the expression of the nir, the nor and the nos genes (Arai et al, 1995(Arai et al, , 1997(Arai et al, , 1999(Arai et al, , 2003 The DNR transcription factor belongs to the CRP/FNR (cAMP receptor protein/fumarate and nitrate reductase regulator) superfamily of regulators (Zumft, 2002;Körner et al, 2003). The members of this superfamily are usually homodimers, each monomer being formed by three domains (McKay & Steitz, 1981): (i) an N-terminal sensing domain (also referred to as the effector domain) with the typical fold of the cAMP-binding domain of CRP; (ii) a long dimerization a-helix recruited to form the dimer interface; and (iii) a C-terminal DNA-binding domain that contains a helix-turn-helix (HTH) motif.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The operon is under the control of Dnr, which is also a DnrD homologue. Although NosR is not necessary in this organism for nosZ transcription, a disruption of nosR halves the promoter activity of the operon (1). Sequence and topological similarities to NosR were also found in CprC, although this protein has a smaller periplasmic domain and lacks the polyferredoxin signature (40).…”
mentioning
confidence: 88%
“…Unfortunately, the mechanism of DnrD activation is still obscure. We can sum up the current situation only thus far: nosR transcription acts positively on its own promoter and activates downstream genes without an operon structure (1,13,21,38,45).…”
Section: Discussionmentioning
confidence: 99%